2020
DOI: 10.1186/s12871-020-01057-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gastric insufflation using LMA-supreme and I-gel versus tracheal intubation in laparoscopic gynecological surgery by ultrasound: a randomized observational trial

Abstract: Background: The application of bedside ultrasound to evaluate gastric content and volume can assist in determining aspiration risk. Applying positive pressure ventilation via supraglottic airway devices (SAD) can result in a degree of gastric insufflation. This study assessed and compared the antral cross-sectional area (CSA) in patients undergoing laparoscopic gynecological surgery when managed with different SAD. Methods: One hundred American Society of Anesthesiologists I or II female patients were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
1
15
1
Order By: Relevance
“…The other method described by Shariffuddin et al was gastric aspirate rather than gastric volume measurement by USG and they found that the gastric volume aspirated with Ambu AuraGain was less and not statistically significant, which was not done in our study [16]. Though the main limitation of SAD is the presence of unprotected airway with the leading risk of aspiration which can be prevented by its correct placement, i.e., its acts as a barrier at the level of upper oesophageal sphincter, and the incidence of aspiration was similar to that of tracheal intubation approximately 0.02% [7,17,18]. However, the antral cross-sectional area was measured in all three LMA's namely LMA supreme, I-gel, and tracheal intubation by Ye et al, and there was no difference, but they failed to find out the gastric volume which helps us to anticipate aspiration following its usage; this is well marked in our study.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…The other method described by Shariffuddin et al was gastric aspirate rather than gastric volume measurement by USG and they found that the gastric volume aspirated with Ambu AuraGain was less and not statistically significant, which was not done in our study [16]. Though the main limitation of SAD is the presence of unprotected airway with the leading risk of aspiration which can be prevented by its correct placement, i.e., its acts as a barrier at the level of upper oesophageal sphincter, and the incidence of aspiration was similar to that of tracheal intubation approximately 0.02% [7,17,18]. However, the antral cross-sectional area was measured in all three LMA's namely LMA supreme, I-gel, and tracheal intubation by Ye et al, and there was no difference, but they failed to find out the gastric volume which helps us to anticipate aspiration following its usage; this is well marked in our study.…”
Section: Discussioncontrasting
confidence: 52%
“…However, the antral cross-sectional area was measured in all three LMA's namely LMA supreme, I-gel, and tracheal intubation by Ye et al, and there was no difference, but they failed to find out the gastric volume which helps us to anticipate aspiration following its usage; this is well marked in our study. And in our study, measured gastric volume was lesser in Ambu AuraGain group than LMA ProSeal group [7].…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…In recent years, the nursing mode in China has gradually changed from “disease-centered” to “patient-centered” [ 17 ]. Based on gynecological malignant tumor surgery and psychological characteristics of patients, targeted nursing intervention is of great significance to postoperative rehabilitation of patients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%